Recent Advances and Mechanistic Insights into Antibacterial Activity, Antibiofilm Activity, and Cytotoxicity of Silver Nanoparticles - Tripathi, Neetu; Goshisht, Manoj Kumar (ACS applied bio materials, 2022)
The substantial increase in multidrug-resistant (MDR) pathogenic bacteria is a major threat to global health. Recently, the Centers for Disease Control and Prevention reported possibilities of greater deaths due to bacterial infections than cancer. Nanomaterials, especially small-sized (size ≤10 nm) silver nanoparticles (AgNPs), can be employed to combat these deadly bacterial diseases. However, high reactivity, instability, susceptibility to fast oxidation, and cytotoxicity remain crucial shortcomings for their uptake and clinical application. In this review, we discuss various AgNPs-based approaches to eradicate bacterial infections and provide comprehensive mechanistic insights and recent advances in antibacterial activity, antibiofilm activity, and cytotoxicity (both in vitro and in vivo) of AgNPs. The mechanistic of antimicrobial activity involves four steps: (i) adhesion of AgNPs to cell wall/membrane and its disruption; (ii) intracellular penetration and damage; (iii) oxidative stress; and (iv) modulation of signal transduction pathways. Numerous factors affecting the bactericidal activity of AgNPs such as shape, size, crystallinity, pH, and surface coating/charge have also been described in detail. The review also sheds light on antimicrobial photodynamic therapy and the role of AgNPs versus Ag+ ions release in bactericidal activities. In addition, different methods of synthesis of AgNPs have been discussed in brief.